PENGARUH INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM DI GOR Hj. AGUS SALIM KOTA PADANG - Siti Nur Azizah; Dewi Zulvia (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
Increased financial literacy and financial inclusion can develop micro and small businesses SMEs) because MSME actors can understand the basic concepts of financial products, good financial planning and management, also protects in the future from fraud and unfair work of financial markets. This research aims to knowing the effect of financial literacy and financial inclusion on work development SMEs in Gor Hj. Agus Salim, Padang City. This study uses a quantitative approach. The data collected from the study were based on interviews and questionnaire distribution withsampling technique is simple random sampling. Data analysis techniques in researchThis is a linear multiple regression analysis with the help of computer SPSS program. Results this study can conclude that financial inclusion has no effect on the performance of MSMEs and financial literacy has a positive effect on the performance of MSMEs in Gor Hj. Agus Salim, Padang City